Empowering rural girls through education: way of reducing vulnerability and improving family economic wellbeing in rural Northern Nigeria - Abdullahi, Ibrahim; Zainalaludin, Zumilah; Paim, Laily (International Organization Of Scientific Research, 2013)
There is perceived decrease in standard of living among some families in the rural area of Katsina State in Nigeria. This was seen to be the result of the inability of some rural families in the area to allowing their daughters to utilize the opportunities of education empowerment program for the rural girls in the State. There is historical evidence that majority of rural girls do not complete primary school talk less of secondary schools and tertiary institutions. These indicate that the rural girls are lagging behind educationally. The issue is the need to educate the girl-child and young women in the rural areas of the country because rural women are the largest and vulnerable group. There are four key elements identified for empowering rural girls and young women; cognitive, resource control, social capital, and awareness or access to information. These important elements have been examined on the wellbeing of women among the families of the empowered rural girls through quantitative study using structured questionnaire. Analysis of these questionnaires shows strong positive correlation between the education empowerment and their economic wellbeing level and significant difference (p<.005) in their lives. This study adds light to understanding impacts of educating girls and women for family and community prosperity and neglecting these can lead to the backwardness. It is also part of growing body of literature from rural sub-Sahara Africa on gender issue. It contributes to the future study on similar topics.